Dose Optimization of Efavirenz Based on Individual CYP2B6 Polymorphisms in Chinese Patients Positive for HIV. (6th April 2016) - Hui, KH; Lee, SS; Lam, TN
Abstract : The purpose of this study was to investigate the impact of CYP2B6‐G516T polymorphisms on the pharmacokinetics (PKs) of efavirenz among the Chinese population and to propose doses for different genotypic populations that optimize therapeutic outcomes. Nonlinear mixed‐effect modeling was applied to describe PKs of efavirenz in Chinese patients with human immunodeficiency virus (HIV). Probabilities of successful treatment at different doses were obtained by simulations using the developed model to identify the optimal doses. The model was based on data from 163 individuals. Efavirenz clearance was found to be significantly influenced by CYP2B6‐G516T polymorphisms and body weight. The typical values of oral clearance were 10.2 L/h, 7.33 L/h, and 2.38 L/h and simulation results suggested that the optimal daily oral doses are 550 mg, 350 mg, and 100 mg for the GG, GT, and TT populations, respectively. The effect of CYP2B6‐G516T polymorphisms on efavirenz clearance was successfully quantified. Pharmacogenetics‐based dose individualization of efavirenz may optimize patient outcomes by promoting efficacy while minimizing central nervous system (CNS) side effects.